1982
DOI: 10.1136/ard.41.5.453
|View full text |Cite
|
Sign up to set email alerts
|

Domiciliary self-measurement in the rheumatoid arthritis and the demonstration of circadian rhythmicity.

Abstract: SUMMARY Symptoms and signs of rheumatoid arthritis vary within the day and from day to day. Interesting and possibly important observations can be missed when evaluations are based only on outpatient measurements, which are likely to be made at only one time and at infrequent intervals. We have found that patients can measure their own grip strength and finger joint sizes at home, and simultaneously assess overall pain and stiffness on numerical scales. Measurements made by patients were reproducible when made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…The symptoms and signs of rheumatoid arthritis vary within and between days (Scott 1960;Delbarre 1979;Kowanko et al 1981Kowanko et al , 1982aHarkness et al 1981Harkness et al , 1982. Although the major symptoms of this common disease are pain, stiffness, and inflammation, systematic investigation of the temporal variation in these have been carried out only on a few occasions (Delbarre 1979;Kowanko et al 1981Kowanko et al , 1982bHarkness et al 1981Harkness et al , 1982.…”
Section: Circadian Rhythm In the Pain Of Rheumatoid Arthritismentioning
confidence: 98%
“…The symptoms and signs of rheumatoid arthritis vary within and between days (Scott 1960;Delbarre 1979;Kowanko et al 1981Kowanko et al , 1982aHarkness et al 1981Harkness et al , 1982. Although the major symptoms of this common disease are pain, stiffness, and inflammation, systematic investigation of the temporal variation in these have been carried out only on a few occasions (Delbarre 1979;Kowanko et al 1981Kowanko et al , 1982bHarkness et al 1981Harkness et al , 1982.…”
Section: Circadian Rhythm In the Pain Of Rheumatoid Arthritismentioning
confidence: 98%
“…For example, pain in rheumatoid arthritis occurs mostly at the beginning of the day (Kowanko et al, 1982) whereas pain due to osteoarthritis occurs mostly at the end of the day (Bellamy et al, 1990). Rigas et al (1990) studied the circadian rhythm of biliary colic in patients undergoing cholecystectomy for symptomatic biliary tract stones.…”
Section: Introductionmentioning
confidence: 99%
“…Pain, functional disability, and stiffness show 24-h rhythms, with a peak in the early morning in many RA patients (31,32), and the rhythms of pain and stiffness may play a role in local and systemic inflammatory responses. Herold and Günther reported that plasma CRP levels, an indicator of inflammatory responses, showed a 24-h rhythm with a peak in the early morning in RA patients, which matched the rhythms of pain and stiffness (33).…”
Section: Discussionmentioning
confidence: 99%